Pengaruh Kualitas Pelayanan Akademik Terhadap Kepuasan Mahasiswa Program Studi Ilmu Pemerintahan Universitas Jambi - M. Ilhamdi (Pusat Riset dan Inovasi Nasional, 2024)
The current phenomenon is that higher education has become a commodity that is needed by society in an effort to improve people's living standards. Where quality tertiary institutions are seen literally by the community from the facilities and infrastructure they have as well as the satisfaction of students within the tertiary institution itself. So the aim of this research is to see the influence of service quality on student satisfaction in the political science study program at Jambi University, both simultaneously and partially. The data used are primary and secondary data. Where primary data was obtained from distributing questionnaires to 85 students who were the research samples. The research method used is a quantitative method, while the research tool used is path analysis. The research results show that there is a significant influence of service quality on student satisfaction, both simultaneously amounting to 75%.